Regional policy at a crossroad: Sweden and Norway on different paths? - Olaf Foss; Steinar Johansen; Mats Johansson; Bo Svensson (European Regional Science Association (ERSA), 2002)
Sweden and Norway are two relatively similar countries in many respects. At a superficial glance, this is true also for the regional policy area. At a closer look, however, there are significant differences and consequently different experiences. An important part of the analysis focuses on how regional policies in Sweden as a member of the EU, and Norway as a non-member, are influenced by European integration. Our main hypothesis is that both countries' regional policy aims and measures move towards the EU's, Sweden's faster than Norway's. The current situation seems to be that Sweden increasingly put its trust into the Structural Fund programmes, while national regional policy is allowed to gradually wither away. To Norway as a non-member of the EU this is not an option, regional policy will have to be carried out within the state framework. While the EU dimension is important for understanding differences in recent tendencies, it should not be taken for granted as the decisive factor in explaining differences. This paper tries to illuminate the regional policy experience, to what extent regional policy has a good or bad image in the two countries, as an alternative explanation to the EU dimension. The argument is that the regional policy experience has been more positive in Norway than in Sweden and that current development must be understood in this light.
Keywords: 330